Aratati ca (1+cos2x)/(1-cos2x)=ctg^2
HawkEyed:
ctg^2 x ?
Răspunsuri la întrebare
Răspuns de
7
(1 + cos²x - sin²x) / (1 - cos²x + sin²x) =
(sin²x + cos²x + cos²x - sin²x ) / (sin²x + cos²x - cos²x + sin²x) =
2cos²x / 2sin²x =
cos²x / sin ²x =
ctg² x ( c.t.d.)
Răspuns de
2
Am atasat o rezolvare.
Anexe:
Alte întrebări interesante
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Informatică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Engleza,
9 ani în urmă